Natural Sesquiterpene Lactones Induce Oxidative Stress in Leishmania mexicana - Barrera, Patricia Andrea (2013)
Leishmaniasis is a worldwide parasitic disease, caused by monoflagellate parasites of the genus Leishmania. In the search for more effective agents against these parasites, the identification of molecular targets has been attempted to ensure the efficiency of drugs and to avoid collateral damages on the host's cells. In this work, we have investigated some of the mechanisms of action of a group of natural sesquiterpene lactones that are effective against Leishmania mexicana mexicana promastigotes. We first observed that the antiproliferative effect of mexicanin I (Mxc), dehydroleucodine (DhL), psilostachyin (Psi), and, at lesser extent, psilostachyin C (Psi C) is blocked by 1.5 mM reduced glutathione. The reducing agent was also able to reverse the early effect of the compounds, suggesting that lactones may react with intracellular sulfhydryl groups. Moreover, we have shown that all the sesquiterpene lactones, except Psi C, significantly decreased the endogenous concentration of glutathione within the parasite. Consistent with these findings, the active sesquiterpene lactones increased between 2.7 and 5.4 times the generation of ROS by parasites. These results indicate that the induction of oxidative stress is at least one of the mechanisms of action of DhL, Mxc, and Psi on parasites while Psi C would act by another mechanism.